Factors that influence advance directives completion amongst terminally ill patients at a tertiary hospital in Kenya. Issue 1 (December 2017) - Omondi, Stephen; Weru, John; Shaikh, Asim; Yonga, Gerald
Abstract Background An advance directive (AD) is a written or verbal document that legally stipulates a person's health care preference while they are competent to make decisions for themselves and is used to guide decisions on life-sustaining treatment in the event that they become incapacitated. AD can take the form of a living will, a limitation of care document, a do-not-resuscitate order, or an appointment of a surrogate by durable power of attorney. The completion rate of AD varies from region to region, and it is influenced by multiple factors. The objectives of this study were to determine the proportion of terminally ill patients with AD and to identify the factors that influence the completion of AD amongst terminally ill patients at a tertiary hospital in Kenya. Methods The study was a retrospective survey. All available records of terminally ill patients seen at Aga Khan University Hospital, Nairobi, between July 2010 and December 2015, and that met the inclusion criteria were included in the study. Results In total, 216 records of terminally ill patients were analyzed: 89 records were of patients that had AD and 127 records were of patients that did not have AD. The proportion of terminally ill patients that had completed AD was 41.2%. The factors that were associated with the completion of AD on bivariate analysis were history of ICU admission, history of endotracheal intubation, functional status of the patient, the medical specialty taking care of the patient, patient's caregiver discussing the AD with the patient, and a palliative specialist review. On multivariate regression analysis, discussion of AD with a caregiver and patient's functional impairment were the factors with statistically significant association with completion of AD. Conclusions The proportion of terminally ill patients that had AD in their medical records was significant. However, most terminally ill patients did not have AD. Our data, perhaps the first on the subject in East Africa, suggest that most of the factors associated with AD completion mirrored those seen in other regions of the world. Discussion between patient and their physician and patient's functional impairment were the factors independently associated with completion of AD. Therefore, physicians need to be aware of the importance of discussions of AD with their patients.